Insecticidal Effects of Organotin(IV) Compounds on Plutella Xylostella (L.) Larvae. II. Inhibitory Potencies Against Acetylcholinesterase and Evidence for Synergism in Tests With Bacillus Thuringiensis(BER.) and Malathion - Ahmad, N.W.; Huang, T.S.; Balabaskaran, S.; Lo, K.M.; Das, V.G. (Hindawi Publishing Corporation, 1994)
Features of pesticide synergism and acetylcholinesterase (AChE) inhibition (in vitro) were studied using a selected range of organotin compounds against the early 4th instar larvae of a highly resistant strain of the diamondback moth (DBM), Plutella xylostella, a major universal pest of cruciferous vegetables.Fourteen triorganotin compounds were evaluated for their ability to enhance the toxicity of the microbial insecticide, Bacillus thuringiensis (BT) and of the commercial insecticide, Malathion to Plutella xylostella larvae. Supplemental synergism was observed with triphenyl- and tricyclopentyltin hydroxides in combinations with Bacillus thuringiensis. Increased synergism was observed with an increase in the number of cyclopentyl groups on tin in the mixed series, Cyp(n) Ph(3-n) SnX, where X = OH, and 1-(1,2,4-triazolyl). The combination of (p-chlorophenyl)diphenyltin N,N-dimethyldithiocarbamate at LD(10) and LD(25) concentrations with sublethal concentrations of Malathion as well as of tricyclohexyltin methanesulphonate at the 0.01% (w/v) concentration with Malathion exerted strong synergistic effects (supplemental synergism) with toxicity index (T.I) values of 7.2, 19.8 and 10.1, respectively.Studies on the in vitro inhibition of acetylcholinesterase prepared from the DBM larvae showed that while most of the triorganotin Compounds tested were without effect on the enzyme, compounds containing the thiocarbamylacetate or the dithiocarbamylacetate moieties demonstrated appreciable levels of inhibition, being comparable in efficacy to commercial grades of Malathion and Methomyl.